Retinal neuroprotection: current strategies and future directions. Issue 3 (May 2019) - Wubben, Thomas J.; Zacks, David N.; Besirli, Cagri G.
Abstract : Purpose of review: Photoreceptor cell death is the ultimate cause of vision loss in many retinal disorders. Currently, there are no commercially available treatments to prevent photoreceptor cell loss and preserve vision, and there is a critical unmet need for neuroprotective modalities to improve photoreceptor survival in a multitude of retinal disorders. This review summarizes the literature published on this topic in the last 18 months. Recent findings: A plethora of novel therapeutic modalities for photoreceptor neuroprotection have recently been examined in clinical trials for age-related macular degeneration, inherited retinal dystrophies, and macular telangiectasia type 2. These modalities include agents that target the complement pathway, stem cells, gene therapies, and neurotrophic factors. Additionally, improved understanding in the metabolic signals that regulate photoreceptor survival and function may ultimately identify targets for developing novel neuroprotective agents in a multitude of retinal disorders. Summary: Retinal neuroprotection is the next frontier in ophthalmic disease, and the discovery of novel neuroprotective strategies will fill a critical unmet need. Although the clinical utility of existing neuroprotective therapies is still quite limited, we are cautiously optimistic in light of the recent successes described in this review as well as other promising developments.